Contribution of physical-chemical variables and passion fruit production in Baixo Acre - Silva de Brito, Rychaellen; Yanet Cáceres Tomaya, Lorena; Andrade Neto, Romeu Carvalho de; Andrade, Reginaldo Almeida; Carvalho, Pedro Henrique da Silva; Chaves, Viviane Pereira (Comunicata Scientiae, 2024)
This study investigated the production and physical and chemical characteristics of eight sour passion fruit genotypes cultivated in Baixo Acre, AC. Evaluation of fruit number (FN), productivity (PRO), longitudinal diameter, transverse diameter (LD and TD), peel thickness (PT), average fruit mass (AFM), pulp mass (PM), juice yield (JY), soluble solids (SS), titratable acidity (TA), ratio, and pH of genotypes H1, H3, R, V1, V2, V3, V4, and V5 was performed. Univariate, multivariate, and Pearson's correlation analyses were performed. Univariate analyses revealed that the genotype H1 stood out in terms of AFM, JY, and PRO; H3 for TD, LD, JY, and pH; H1, H3, V1, and R for LD; H3 and V5 for pH; and V4 and V5 for NF. A strong positive correlation was observed among the physical variables AFM, PM, LD, and TD. Four genotypes groups were obtained for both genetic divergence and PCA. The H1 genotype presented higher productivity, and the H3 genotype presented better fruit physical attributes.